Experimental study on characteristics of pressurized grade conversion of coal. (15th December 2018) - Zhou, Guanwen; Zhong, Wenqi; Yu, Aibing; Dou, Yuanyuan; Yin, Junping
Highlights: Experimental system of pressurized grade conversion of coal was established. General properties of coal and semi-coke were studied. The tar yield reaches its maximum when the pyrolysis temperature is 600 °C. The NO and SO2 emissions decrease with the pressure increases. Abstract: In order to investigate the characteristics of pressurized grade conversion of coal, an experimental system was established, and the general properties of coal and semi-coke were studied by using the BET and SEM methods. Then, the effects of the following variables on production yields, pollutant gas emission, and the quality of high-grade raw materials such as tar and coal gas were investigated in the ranges as specified: pyrolysis temperature (500–700 °C), pressure (0.1–0.5 MPa), pyrolysis atmosphere (N2 and coal gas) and particle size (0–3 mm and 0–6 mm). It was found that when the coal pyrolysis temperature is 600 °C, the tar yield reaches its maximum, and the coal gas atmosphere and pressure are both helpful to increase the tar and semi-coke yield as well as to improve the quality of tar and the heat value of coal gas. With the pressure increasing, the NO and SO2 emissions decrease. As a result of the pressure increase, the combustion temperature of the semi-coke decreases, resulting in the reduction of high temperature minerals and the increase of low temperature minerals in ash. The results of this study will be useful to address some of the presently existing issues in design, optimization and scale up of pressurized grade conversion of coal processes.